Hubungan Inisiasi Menyusu Dini dengan Penurunan Perdarahan Post Partum dan Proses Involusio Uteri di PMB Supiani - Pasaribu, Miraria Rosalina; Silaban, Verawaty Fitrinelda; Sitorus, Ester Rosalia Lasma; Alriyanti, Alriyanti; Siregar, Dina Adelia; Purba, Agina Timanta Br (Journal of Pharmaceutical and Sciences, 2025)
Background: The postpartum period is a critical time for mothers. Postpartum hemorrhage and delayed uterine involution are complications that can increase maternal morbidity and mortality. Early Breastfeeding Initiation (EBI) is hypothesized to prevent these complications by stimulating the release of oxytocin, which triggers uterine contractions. Objective: This study aimed to analyze the relationship between the implementation of EBI and the reduction of postpartum hemorrhage and the acceleration of uterine involution at PMB Supiani. Methods: This research employed a cross-sectional design with a quantitative approach. The sample consisted of 80 postpartum mothers selected using a purposive sampling technique. Data were collected using an observational questionnaire and analyzed using the Chi-Square statistical test to identify relationships between variables. Results: A total of 87.5% of respondents performed EBI. The analysis results showed a significant relationship between EBI and reduced postpartum hemorrhage (p-value = 0.001) and between EBI and accelerated uterine involution (p-value = 0.001). Mothers who performed EBI tended to experience normal bleeding and a faster uterine involution process. Conclusion: EBI has a significant relationship with the reduction of postpartum hemorrhage and the acceleration of uterine involution. Therefore, education and support to encourage the implementation of EBI in delivering mothers are essential to prevent postpartum complications.